Adaptation of Using Instagram For Brand Awareness of Porcelain Tableware Products : A Case Study @zentableware - Wulandari, Catur; Putra, Afdal Makkuraga; Jamil, Achmad (IJOSMAS, 2023)
This study aims to analyze the adaptation methode of brand awareness porcelain tableware product using new media Instagram . Zentableware is a Indonesia local brand of porcelain tableware. Has domestic market with targetting upper middle market and International market for Asian Countries. With potential and strength of product development, design, production facilities, production capacity made Zentableware growth easily. For enlarge the brand recognition,prompotion and brand awareness, they are need supports from new media such Instagram to reach the target market. Instagram as new media has good visual appearance and supporting features to support as tools of brand awareness. The background of research and purpose of this research are to provide an input to wider audiences and companies how to be using instagram as tool of brand awareness and promotion.This research was conducted from October 2021 to October 2022. This research used a qualitative research method, and konstruktivsm paradigm with case study by describing the phenomena that occur in the zentableware business such as tacticts uses as strategi brand awareness through Instagram. Data collection techniques were carried out by deep interview of Key Informan and observation Instagram @zentableware. According to McQuail, New Media is telematics media which is a different set of electronic technologies with different uses.